O-018 Sperm count is increased by diet-induced weight loss and maintained by exercise or GLP-1 analogue treatment: a randomised controlled trial. (30th June 2022) - Andersen, E; Juhl, C R; Kjøller, E T; Lundgren, J R; Janus, C; Saupstad, M; Ingerslev, L R; Jensen, S B K; Holst, J J; Stallknecht, B M; Madsbad, S; Torekov, S S; et al.
Abstract: Study question: Does diet-induced weight loss improve semen parameters, and are these possible improvements maintained with sustained weight loss? Summary answer: An 8-week low-calorie diet-induced weight loss was associated with improved sperm count, which was maintained after one year in men who maintained weight loss. What is known already: Obesity is associated with impaired semen parameters. Weight loss improves metabolic health in obesity, but there is a lack of knowledge on the acute and long-term effects of weight loss on semen parameters. Study design, size, duration: This is a substudy of men with obesity enrolled in a randomised, controlled, double-blinded trial (the S-LITE trial). The trial was conducted between August 2016 and November 2019. A total of 56 men was included in the study and assigned to an initial 8-week low-calorie diet (800 kcal/day) followed by randomisation to 52 weeks of either: placebo, exercise training, and placebo (exercise), the GLP-1 analogue liraglutide (liraglutide) or liraglutide in combination with exercise training (combination). Participants/materials, setting, methods: Inclusion criteria were men who delivered semen samples, 18 to 65 years of age and a body mass index between 32 to 43 kg/m 2, but otherwise healthy. The study was carried out at Hvidovre Hospital and at the University of Copenhagen, and the participants were from the Greater Copenhagen Area. We assessed semen parameters, anthropometrics and collected blood samples before (T0) and after the 8-week low-calorie dietary intervention (T1) and after 52 weeks (T2). Main results and the role of chance: The men lost on average 16.5 kg (95% CI: 15.2-17.8) bodyweight during the low-calorie diet, which increased sperm concentration 1.49 fold (95% CI: 1.18-1.88, P <0.01) and sperm count 1.41 fold (95% CI: 1.07-1.87, P <0.01). These improvements were maintained for 52 weeks in men who maintained the weight loss but not in men who regained weight. Semen volume, sperm motility and motile sperm count did not change. Limitations, reasons for caution: The S-LITE trial was a randomised controlled trial of weight loss maintenance. Analysis of semen was preregistered to explore the effects of weight loss and weight loss maintenance on semen parameters. Due to the small sample size, definite inferences cannot be made. Wider implications of the findings: This study shows that sperm concentration and sperm count were improved after a diet-induced weight loss in men with obesity. Our findings indicate that both liraglutide and exercise as weight maintenance strategies may be used to maintain the improvements in sperm concentration and count. Trial registration number: H-16027082